OPTIMALISASI LABA PERUSAHAAN MELALUI EFISIENSI BIAYA PRODUKSI - M. Avifan Rusli; Rumanintya Lisaria Putri (Universitas Trunojoyo Madura, 2015)
Up to now there is still a debate on environmental issues, which is caused by increased economic activity both in the number of industrial enterprises in operation, utilization of natural resources is increasing and the rate of exploitation led to an increase in the number and quality of the waste. Some people began to realize as a result of the disposal of waste into the environment, so we need to think about how waste can be processed and do not pollute the environment. At the Ngadiredjo sugar mill the waste that generated would be processed into products that have a high selling price. From the analysis of the researcher, the Ngadiredjo sugar mill waste submit the results to the Sumberlumbu as processing waste into compost. Proceeds from the sale of compost was not given to PG Ngadiredjo because Sumberlumbu unit is no longer the cooperation unit of PG Ngadiredjo. The results of percentage cost assessment, in 2013 had a cost increase of 4.24% compared to the year 2012, while in 2014 the cost increase to 20.75%. Comparison of the percentage increase in the company's profit PG Ngadiredjo in 2012 until 2014, by calculating other income resulting from the processing of waste is used as compost. Assessment results are affected by the increase in profit from the sale of compost in 2012 is 1.402% from the general profit, the 2013 is 2.92% of earnings, 2014 was 3.44% of the profit. If the revenue from compost combined, the percentage of profit increase of 3.57% from Rp 61.428.934.000, - be Rp63.614.647.000, -.